Study Of Variations In Serum Lipid Profile And Transaminase Levels In Overt Hypothyroidism - DR. D.V.KRISHNAVENI (International Journal of Pharma and Bio Sciences, 2011)
This study was undertaken to evaluate the variations in thyroid profile, lipid profile and transaminase levels in overt hypothyroid patients, compared to healthy controls. Thirty hypothyroid patients, both male & female, in the age group of 20 to 50 years (study group) and 30 age & sex matched healthy subjects (control group) were enrolled in the study. We found significant increase in mean levels of total cholesterol, serum triglycerides, LDL-c, AST & TSH and significant decrease in T3 & T4 in study group compared to controls. There was no significant difference in HDL –c values between two groups. The ALT and VLDL-c values were near the upper limits of normal range in study group, while they were near the lower limit in control group, the difference being significant.